(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize and compare recent evidence on coronary artery lesion characteristics in patients with chronic coronary syndrome, and to analyze the associations between cardiovascular risk factors and lesion morphology. Subjects and methods: This narrative review included English and Vietnamese articles published from January 2023 to October 2025 and identified through PubMed, Google Scholar, and Web of Science. A total of seven studies involving patients with chronic coronary syndrome diagnosed by invasive coronary angiography or coronary computed tomography angiography were included. Results: In patients with chronic coronary syndrome, coronary lesions were most frequently located in the left anterior descending artery, with a higher prevalence among those with diabetes mellitus, hypertension, or dyslipidemia. Dyslipidemia was identified as an independent risk factor associated with multivessel disease and more severe coronary lesions. The prevalence of left main disease and chronic total occlusion ranged from 4.9% to 17.8%, predominantly in older male patients. High-risk plaque features showed prognostic value for major adverse cardiovascular events. Several studies suggested that revascularization strategies should be individualized according to lesion complexity and clinical characteristics. Conclusion: Chronic coronary syndrome is commonly associated with complex coronary lesions and is influenced by multiple cardiovascular risk factors. Comprehensive assessment of lesion characteristics together with optimal control of risk factors plays an important role in guiding management and improving prognosis.